Análisis Financiero a la Junta Administradora de Agua Potable de los Barrios San Jose, Mollepamba, Izhcayluma, Puliche y el Salado, Periodo 2021-2022 - Bejarano Macanchi, Mayra Alejandra (2025)
This Curricular Integration Work called “Financial Analysis to the Board of Directors of the Potable Water Administration of the Neighborhoods San José, Mollepamba, Izhcayluma, Puliche and El Salado, period 2021-2022”, was developed with the purpose of fulfilling the objectives proposed when analyzing the financial-economic structure of the Board. In order to meet the objective, the Vertical and Horizontal Analysis was applied to the Financial Statements to determine the economic-financial structure, as well as the variations generated from one period to another of the accounts that comprise it. The results revealed that the Board has sufficient liquidity to pay its short-term debts, in the year 2021 it was underfinanced by third persons, its liabilities had a value of $4,678.33 and in the year 2022 this value was reduced to $4,183.83 dollars. In the year 2021 revenues exceeded costs and expenses, resulting in a profit of $3,517.33, by the year 2022 expenses exceeded revenues, thus giving it a profit of -$58.55. The Liquidity Indicators were applied and it was evidenced that the Board has sufficient liquidity to cover its short-term obligations, in the year 2021 it has $25.87 for each dollar owed and for the year 2022 it has $29.93. However, the Activity Indicator revealed that it was not efficient in the management of inventories since for the year 2021 the inventory turnover was 1.22 times and for the year 2022 it was 0.94 times. As for indebtedness, a decrease in its debts was observed, since for the year 2021 the level of indebtedness was 1.12% and for the year 2022 it was 0.97%. The report was prepared detailing conclusions and recommendations, aimed at improving the operation of the Junta Administradora de Agua Potable, to contribute to future decision making by its partners, in order to strengthen the activities, it is important to implement sales policies: To expand the services of the Board to sectors such as: Chiquinda, Yasanga and Lambonuma areas that currently do not have access to drinking water and thus increase demand. The methodology used in the vertical and horizontal analysis and financial indicators were established: Analytical Method; allowed to analyze and interpret of the information obtained, after applying financial techniques and tools. Synthetic Method; it was used to prepare a financial analysis report in a clear and precise manner, containing conclusions and recommendations. Mathematical Method; it was used to calculate formulas, which allowed to obtain the real results and to make a data comparison. Statistical Method; it was applied to the handling of qualitative and quantitative data of the financial analysis, it allowed to compile and analyze the information and later represent it in tables and graphs, to facilitate the interpretation 5 of each of the data.